معوقات العملية التعليمية وإمكانيات تطبيق إدارة الجودة الشاملة بالطور الابتدائي في ظل الوضع الراهن - فرحات, بلقاسم; محدة, بالقاسم (University of Eloued جامعة الوادي, 2020)
هدفت هذه الورقة البحثية إلى إبراز واقع التعليم في الطور الابتدائي والمشاكل التي يعاني منها في سبيل تحقيق الأهداف المرجوة، وذلك بالتركيز على أهم الدراسات الجزائرية التي اهتمت بهذا الجانب، إضافة إلى التطرق إلى امكانيات تطبيق إدارة الجودة من أجل تحسين جودة كافة عناصر العملية التعليمية بالمدرسة الجزائرية، وذلك من خلال التطرق إلى مبرراتها وسبل نجاحها ومعوقات تطبيقها. وقد أوصت هذه الورقة البحثية على ضرورة إعادة الاعتبار والتقويم الشامل لمكونات العملية التعليمية للطور الابتدائي باعتباره أهم ركائز النظام التعليمي والتربوي. Abstract: This research paper aims to highlight the reality of education in the primary education and the problems it suffers in order to achieve the desired goals, by focusing on the most important Algerian studies that have been interested in this aspect, In addition to addressing the possibilities of the application of quality management in order to improve the quality of all elements of the educational process in the Algerian school, And by addressing the justifications and ways of success and obstacles to their application. This paper recommended the necessity of re-consideration and comprehensive evaluation of the components of the educational process of the primary education as the most important pillars of the educational system.
Obstacles of the educational process and the possibilities of the application of total quality management in the primary education in the current situation.
الملتقى الوطني الأول حول المدرسة الجزائرية الإشكالات والتحديات 18- 19 فيفري 2020. جامعة الوادي
Keywords: التعليم الابتدائي، الجودة، العملية التعليمية، جودة العملية التعلمية، مشكلات التعليم.; Primary education, Quality, Educational process, Quality of educational process, Education problems